2012
DOI: 10.1038/ncomms1708
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres are favoured targets of a persistent DNA damage response in ageing and stress-induced senescence

Abstract: Telomeres are specialized nucleoprotein structures, which protect chromosome ends and have been implicated in the ageing process. Telomere shortening has been shown to contribute to a persistent DNA damage response (DDR) during replicative senescence, the irreversible loss of division potential of somatic cells. Similarly, persistent DDR foci can be found in stress-induced senescence, although their nature is not understood. Here we show, using immuno-fluorescent in situ hybridization and ChIP, that up to half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
769
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 766 publications
(808 citation statements)
references
References 40 publications
34
769
2
3
Order By: Relevance
“…5; Figs S3–6). In some cases, there were changes shortly after irradiation, consistent with potential acute responses to radiation, while senescence becomes established after days or weeks (Hewitt et al ., 2012). Bcl‐xl and Bcl‐2 increased in HUVECs, IMR90 cells, and MEFs but not preadipocytes, suggesting that senescent HUVECs, IMR90 cells, and MEFs might depend more on this pro‐survival pathway than N‐resistant preadipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…5; Figs S3–6). In some cases, there were changes shortly after irradiation, consistent with potential acute responses to radiation, while senescence becomes established after days or weeks (Hewitt et al ., 2012). Bcl‐xl and Bcl‐2 increased in HUVECs, IMR90 cells, and MEFs but not preadipocytes, suggesting that senescent HUVECs, IMR90 cells, and MEFs might depend more on this pro‐survival pathway than N‐resistant preadipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…However, since not all cells with DDR foci expressed high levels of α‐SMA in stress fibers (Supporting Information Figure S3d), our data also suggested that activation of the DDR alone is not sufficient for myofibroblast transdifferentiation and that other factors, such as timing of DDR induction or long‐term persistence of the DDR, are critical for activating the transdifferentiation program. As dysfunctional telomeres activate a persistent DDR while nontelomeric DSBs are repaired within minutes of being generated (Fumagalli et al, 2012; Hewitt et al, 2012), we tested whether fibroblasts are stimulated to transdifferentiate preferentially due to a persistent telomeric DDR. By simultaneously immunostaining TGF‐β1‐treated cells for α‐SMA expression and TIF formation, we discovered that the great majority of α‐SMA‐expressing myofibroblasts indeed displayed dysfunctional telomeres and were TIF positive (75%).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, telomere dysfunction‐induced senescence (TDIS) can also be triggered in the absence of continuous cell proliferation and in the absence of critical telomere shortening. For example, genotoxic stresses that cause DSB formation in telomeric repeats can rapidly activate TDIS, as telomeric breaks resist DNA repair activities (Fumagalli et al, 2012; Hewitt et al, 2012; Suram et al, 2012). Stresses that have been demonstrated to cause TDIS include oncogene expression (Patel, Suram, Mirani, Bischof, & Herbig, 2016; Suram et al, 2012), DNA replication stress (Boccardi et al, 2015; Fumagalli et al, 2012; Hewitt et al, 2012), and reactive oxygen species (ROS) (Boccardi et al, 2015), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAF + (telomere‐associated foci) nuclei were used as a marker of senescent cell burden (Hewitt et al ., 2012). TAF + nuclei were readily evident in subpopulations of cells in aorta (and localized in both endothelial and smooth muscle layers in the vessel wall) from vehicle‐treated mice (Fig.…”
Section: Can Chronic Senolytic Treatment Improve Age‐related Vascularmentioning
confidence: 99%